Politik Hukum Pencegahan Korupsi Melalui Pembatasan Hak Politik Eks Narapidana Korupsi - Andryan Andryan; Benito Asdhie Kodiya (Universitas Medan Area, 2020)
Indonesia's Corruption Perceptions Index (IPK) in 2018, put Indonesia up seven places to position 89 out of 180 countries. The increase in the ranking is a breath of fresh air in fighting corruption in Indonesia. As for the breakthroughs made in creating a deterrent effect on criminal acts of corruption, namely by depriving political rights through judges' decisions in court. Prohibition of former convicts in cases of corruption, drug dealers, sexual crimes against children, becoming candidates for legislative candidates (bacaleg) in the 2019 Election. restrictions on political rights, on the one hand there are those who are against restrictions on political rights which are considered to injure human rights. Revocation of political rights is considered to be a legal construction in eradicating criminal acts of corruption, where the revocation of the right to be elected is carried out in order to prevent the election of leaders who have been involved in corruption in public positions. Among the fundamental rights, one of which is affirmed in Article 28D paragraph (3) of the 1945 Constitution,